Primary colorectal lymphomas - Stanojević Goran; Stojanović Miroslav; Jovanović Milan; Stojanović Miodrag; Jeremić Miroslav; Branković Branko; Ignjatović Nebojša; Katić Vuka V. (Vojnosanitetski Pregled)
Background/Aim. Colorectal lymphoma is a rare tumor representing 1.4% of human lymphomas, 10-20% of gastrointestinal lymphomas, namely 0.2-0.6% of all malignancies in the colon. The aim of this study was to review clinical characteristics of primary colorectal lymphoma and overall survival. Methods. A detailed analysis of 16 surgically treated patients included patients age, symptoms and signs, tumor site, type of surgery, histopathologic findings, diagnosis of the disease, disease stage, type of surgery related to the degree of emergency (elective or urgent), applied adjuvant therapy, patient follow-up and treatment outcomes. Survival was expressed by the Kaplan-Meier curve, while the difference in survival among the two groups by the Log-rank test. Results. The all patients were on an average followed-up for a median of 29 months (range 2-60 months), while those with chemotherapy 48 months (range 4-60 months). An overall mean survival time was 38.65 months. Conclusion. Primary colorectal lymphoma is a rare malignant tumor of the large bowel. Therapy usually involves resection of the affected colon or rectum and regional lymphovascular structures, followed by adjuvant therapy. Survival period is short and, therefore, timely diagnosis is crucial in early disease stages when the probability of cure is high.